JURIDICAL REVIEW OF THE DECISION OF BANDUNG DISTRICT COURT NO. 166/PDT/G/1991/PN.BDG AFTER THE AMENDMENT OF LAW NO. 7 OF 1989 - Maskur; Hermansyah; Ade Suherman; Prima Melati (Institut Pendidikan Indonesia, 2023)
Judicial competence within the scope of judicial power includes general and religious courts. The explanation in Law No. 7 of 1989 regarding religious courts still provides a choice of law for those who litigate and adhere to Islam. This study aims to determine the legal position of the Bandung District Court decision No. 166/Pdt/G/1991/PN.BDG after the amendment of Law No. 7 of 1989. The research method used is descriptive analytical by using literature study and using secondary and primary legal sources and interviews. The results showed that the decision of the Bandung District Court No. 166/Pdt/G/1991/PN.BDG was based on the competence of the Religious Courts contained in Law No. 3 of 2006 after the amendment of Law No. 7 of 1989 regarding Religious Courts. Bandung District Court Decision No. 166/Pdt/G/1991/PN.BDG is null and void because the settlement of property and inheritance disputes for those who are Muslims must be resolved through the Religious Court because Law No. 3 of 2006 does not recognize the choice of law for those who are Muslims in resolving property and inheritance disputes as previously regulated in Law No. 7 of 1989.